Potensi Reduksi Emisi Gas Rumah Kaca dan Kelayakan Finansial dari Pembangkit Listrik Tenaga Mikro Hidro Cisalimar, Jawa Barat - Siti Allifah; Pini Wijayanti (Jurnal Ilmu Lingkungan)
The energy sector related activities have increased greenhouse gas (GHG) emissions and global temperatures. The implementation of green energy as mitigation efforts to reduce GHG emissions are required to reduce the negative impacts of climate change, but they are costly. Micro Hydro Power Plant (MHP) is one of green energy that supports the Sustainable Development Goals (SDGs) in rural areas. This study aims to estimate the potential GHG emissions prior the establishment of Cisalimar MHP project, the GHG emission reduction after the project, and to analyze the financial feasibility of the project. The Clean Development Mechanism (CDM) method is used to estimate the potential for GHG emission reductions, meanwhile the financial feasibility is employed to evaluate the financial feasibility of the project. The results show that GHG emissions without the MHP project were 25,50 t CO2 per year in 2005 and may increase to 34,39 t CO2 per year in 2030. Cisalimar MHP can reduce GHG emissions from 99,87% to 99,91% within the period of 2005-2030. However, such emission reduction requires a considerable cost i.e., USD 76.044,11. Financially, Cisalimar MHP is not feasible due to high investment costs but can reduce GHG emissions as well as contribute to the achievement of SDGs in remote villages.